Five Decades of Global Chemical Terror Attacks: Data Analysis to Inform Training and Preparedness. (24th December 2021) - DeLuca, Michael A.; Chai, Peter R.; Goralnick, Eric; Erickson, Timothy B.
ABSTRACT: Background: Chemical weapons attacks during the recent conflict in Syria and Iraq highlight the need to better understand the changing epidemiology of chemical weapons use, especially among non-state actors. Public health professionals and policy-makers require this data to prioritize funding, training, chemical weapons preparedness, disaster response, and recovery. The purpose of this investigation is to provide descriptive data that can be used by policy-makers and public safety officials to better prepare for these potential attacks. Methods: A five-decade descriptive retrospective review of The Global Terrorism Database, maintained by the National Consortium for the Study of Terrorism and Responses to Terrorism, was conducted to understand trends in chemical agents, targets, and routes of exposure. We reviewed and analyzed data specific to these documented chemical attacks between 1970 and 2017. Results: 383 terror attacks involved chemical weapons over the study period. A specific agent was named in 154 incidents, while 124 incidents could be classified into traditional chemical weapons categories (eg, vesicant, choking agents). A route of exposure was identified in 242 attacks, with the most common routes of exposure being dermal-mucosal and inhalational. Caustic agents were used in the highest portion of attacks (25%) where the route of exposure was known. Explosive devices were used in 21% of attacks to deliver these chemical agents. Of particular note, private citizens and educational facilities were targeted in 25% and 12% of attacks, respectively. The average number of attacks increased from 6 per year between 1970 and 2011 to 24.9 per year between 2011 and 2017 (coinciding with the start of the Syria conflict). The most commonly utilized chemicals were chlorine (26.0%), tear gas (20.8%), and cyanide (15.6%). Blood agent incidents declined from 32.6% before the September 11, 2001 attacks to 13.6% after 2001, while nerve agent attacks fell from 9.3% to 1.2%. In contrast, choking (namely chlorine) and vesicant (mustard) agent use increased from 7% to 48.1% and from 2.3% to 6.2% of attacks, respectively. Conclusions: Chemical weapon use in global terrorism remains an increasingly common occurrence that requires better characterization. The average number of chemical terrorist attacks per year is increasing, with a large proportion resulting from the conflicts in Iraq and Syria. Choking (chlorine) and vesicant (mustard) agents have become the predominant chemical terror agent since 2001, with a decreased incidence of blood (cyanogenic) and nerve (sarin) agents. Future preparedness initiatives should focus on vulnerable targets such as private citizens and educational institutions. Improving blast injury response is essential, along with prioritizing disaster training focused on choking agents, vesicants, and caustics.